(untitled) (Journal of economic and management development research, 2025)
Against the backdrop of the deep interweaving of the digital economy and supply chain restructuring, archive digitalization, as the core carrier of data factorization, has become a key path to address information asymmetry in the supply chain and enhance its resilience. From an interdisciplinary perspective of management science, this study aligns with the policy orientations of the 14th Five-Year Plan for the Development of National Archives Undertakings and the Guidelines for Improving the Supply Chain Management Level of Manufacturing Enterprises, focusing on the collaborative dilemmas of archive digitalization between core enterprises and small-to-medium-sized suppliers. A two-stage evolutionary game model incorporating variables of outsourcing costs and policy subsidies is constructed to analyze the equilibrium conditions of strategy choices for both parties. The research is validated using panel data of the digital archive processing industry from 2021 to 2025 (market size: 4.8 billion to 16 billion yuan) and the Changhong supply chain case. Results indicate that three key variables drive the collaborative digitalization of supply chain archives: the digital spillover effect of core enterprises (elasticity coefficient: 0.72), the Shapley value-based cost-sharing ratio (45%-65%), and policy subsidy intensity (accounting for more than 15% of collaborative costs). When the collaborative benefit coefficient is ≥ 0.65, both parties will form a stable equilibrium of "co-construction and sharing", reducing the supply chain disruption recovery cycle by 22% and the operational loss rate by 30%. This study constructs an analytical framework of "policy guidance - interest coordination - resilience enhancement", enriches the application scenarios of game theory in supply chain digital transformation, and provides dual references for enterprise practice and policy formulation, meeting the theoretical depth and empirical requirements for publication in CSSCI-indexed journals.